Agent Banking in a Highly Under-Developed Financial Sector : Evidence from the Democratic Republic of Congo - Cull, Robert (World Bank, Washington, DC, 2017)
The paper provides evidence on the number and volume of financial transactions undertaken by agents (local businesses that double as more convenient, lower cost alternatives to formal branches) of the largest microfinance institution operating in the Democratic Republic of Congo. More important than agents’ personal characteristics, transactions are higher in low-income, densely populated areas with high levels of commercial development. This finding suggests that the agent network has been best at supporting financial transactions among the urban poor. In addition, branding and effective liquidity management are strongly linked to agent activity.